(untitled) (Applied Biological Research, 2017)
A study was conducted to investigate association of body condition-score (BCS) with serum biochemical profile and body morphometry of cross bred cows. Crossbred cows of same parity were selected randomly and grouped into three categories of 6 animals each, based on body condition score (BCS) [2-3 (A), 3-4 (B) and >4 (C)] at MLRI, Mansbal (Kashmir). Blood samples were collected from these animals at 5 stages viz., 15 days prepartum (stage I); and 5th day (stage II), 15th day (stage III), 30th day (stage IV) and 45th day (stage V) postpartum. Highest BCS was observed at stage I in all the groups and lowest at stage IV in group A and stage V in groups B and C. Serum glucose was highest at stage I in all the groups but significantly decreased at stage II. Serum urea showed highest value at stage IV. Total protein and albumin contents in all groups increased with progress of lactation. Total cholesterol was lowest at stage I in group B and C and at stage II in group A. Body length didn’t differ among the various BCS groups. Chest girth and pelvic girth varied significantly within BCS groups with highest values of BCS in group C.